The Quality of Social and Health Care Services from the Perspective of Elderly People Belonging to Ethnic Minorities - Hämäläinen, Taija (2009)
Only abstract. Paper copies of master’s theses are listed in the Helka database (http://www.helsinki.fi/helka). Electronic copies of master’s theses are either available as open access or only on thesis terminals in the Helsinki University Library. Vain tiivistelmä. Sidottujen gradujen saatavuuden voit tarkistaa Helka-tietokannasta (http://www.helsinki.fi/helka). Digitaaliset gradut voivat olla luettavissa avoimesti verkossa tai rajoitetusti kirjaston opinnäytekioskeilla. Endast sammandrag. Inbundna avhandlingar kan sökas i Helka-databasen (http://www.helsinki.fi/helka). Elektroniska kopior av avhandlingar finns antingen öppet på nätet eller endast tillgängliga i bibliotekets avhandlingsterminaler. This study aimed at researching the quality of social and health care services from minority ethnic older persons' perspective. This was done by identifying the dimensions of the services where quality was experienced as poorest as well as studying the factors that influenced the experienced quality of the services. The client based quality was analysed as the congruence between the clients' expectations and perceptions. The information gathered from elderly people belonging to ethnic minorities was compared with data from social and health care service personnel. With the help of the analyses of experienced quality, the study aimed at identifying ways to develop and organise the social and health care services so that they would provide high quality services also for the elderly clients belonging to ethnic minorities. The data of this study consisted of two samples. The service user sample included constructed interviews with 119 Russians, 50 Vietnamese and 126 Sami respondents. The service provider sample consisted of 71 respondents, from whom data were gathered by postal survey with a questionnaire. Both of the samples were analysed by using quantitative, statistical methods. The area where quality was experienced as poorest, both among the service users and service providers, was access to services. The ...